Real-Time fMRI Neurofeedback in Patients With Tobacco Use Disorder During Smoking Cessation: Functional Differences and Implications of the First Training Session in Regard to Future Abstinence or Relapse - Karch, Susanne; Paolini, Marco; Gschwendtner, Sarah; Jeanty, Hannah; Reckenfelderbäumer, Arne; Yaseen, Omar; Maywald, Maximilian; Fuchs, Christina; Rauchmann, Boris-Stephan; Chrobok, Agnieszka; Rabenstein, Andrea; Ertl-Wagner, Birgit; et al. (Frontiers in Human Neuroscience, 2019)
One of the most prominent symptoms in addiction disorders is the strong desire to consume a particular substance or to show a certain behaviour (craving). The strong association between craving and the probability of relapse emphasises the importance of craving in the therapeutic process. Former studies have demonstrated that neuromodulation using real-time fMRI (rtfMRI) neurofeedback (NF) can be used as a treatment modality in patients with tobacco use disorder. The aim of the present project was to determine whether it is possible to predict the outcome of NF training plus group psychotherapy at the beginning of the treatment. For that purpose, neuronal responses during the first rtfMRI NF session of patients who remained abstinent for at least three months were compared to those of patients with relapse. All patients were included in a certified smoke-free course and took part in three NF sessions. During the rtfMRI NF sessions tobacco-associated and neutral pictures were presented. Subjects were instructed to reduce their neuronal responses during the presentation of smoking cues in an individualised region of interest for craving (anterior cingulate cortex (ACC), insula or dorsolateral prefrontal cortex). Patients were stratified to different groups (abstinence [N=10] vs. relapse [N=12]) according to their individual smoking status three months after the rtfMRI NF training. A direct comparison of BOLD responses during the first NF-session of patients who had remained abstinent over three months after the NF training and patients who had relapsed after three months showed that patients of the relapse group demonstrated enhanced BOLD responses, especially in the ACC, the supplementary motor area as well as dorsolateral prefrontal areas, compared to abstinent patients. These results suggest that there is a probability of estimating a successful withdrawal in patients with tobacco use disorder by analysing the first rtfMRI NF session: a pronounced reduction of frontal responses during NF training in patients might be the functional correlate of better therapeutic success. The results of the first NF sessions could be useful as predictor whether a patient will be able to achieve success after the behavioural group therapy and NF training in quitting smoking or not.